Representation of logarithm of entire function in several complex variables - Brodyak O.Ya; Vasyl'kiv Ya.V. (Karpats'kì matematinì publìkacìï, 2012)
The integral representation of some branch of an entire on $mathbbC^n$function which generalized the Poisson-Jensen-Stoll Formula is obtained.